Gauge theory on Calabi-Yau manifolds - Thomas, R; Richard P. W. Thomas (1997)
We study complex analogues on Calabi-Yau manifolds of gauge theories on low dimensional real manifolds. In particular we define a holomorphic analogue of the Casson invariant, counting coherent sheaves on a Calabi-Yau 3-fold.